Former Yugoslav Republic of Macedonia : Country Fiduciary Assessment - World Bank (Washington, DC, 2012)
This Country Fiduciary Assessment (CFA) follows upon the Country Financial Accountability Assessment (CFAA) issued in 2003 and the Country Procurement Assessment Report (CPAR) issued in 2002. Because procurement is integral to the concept of public financial management (PFM), this CFA integrates procurement and financial management assessment into a single report. The report has three objectives: first is to provide the Bank and other donors with an updated assessment of fiduciary progress since 2003. This includes: (i) fiduciary risk related to the budget environment in the former Yugoslav Republic of Macedonia; and (ii) need for supporting meaningful progress, possibly through future development policy lending instruments. The second objective is to assist the government in its commitment to Public Financial Management (PFM) reforms to secure more efficient and effective use of public sector resources. Finally, the third is to help the government measure progress in procurement reform by comparing operations with international standards, providing information to monitor system performance and identifying weaknesses.